A green-gray path to global water security and sustainable infrastructure - Vorosmarty, C.J.; Stewart-Koster, B.; Green, P. A.; Boone, E. L.; Florke, M.; Fischer, Gundula; Wiberg, David A.; Bunn, S. E.; Bhaduri, A.; McIntyre, P. B.; Sadoff, C.; Liu, H.; et al. (Elsevier, 2021)
Sustainable development demands reliable water resources, yet traditional water management has broadly failed to avoid environmental degradation and contain infrastructure costs. We explore the global-scale feasibility of combining natural capital with engineering-based (green-gray) approaches to meet water security threats over the 21st century. Threats to water resource systems are projected to rise throughout this period, together with a significant expansion in engineering deployments and progressive loss of natural capital. In many parts of the world, strong path dependencies are projected to arise from the legacy of prior environmental degradation that constrains future water management to a heavy reliance on engineering-based approaches. Elsewhere, retaining existing stocks of natural capital creates opportunities to employ blended green-gray water infrastructure. By 2050, annual engineering expenditures are projected to triple to $2.3 trillion, invested mainly in developing economies. In contrast, preserving natural capital for threat suppression represents a potential $3.0 trillion in avoided replacement costs by mid-century. Society pays a premium whenever these nature-based assets are lost, as the engineering costs necessary to achieve an equivalent level of threat management are, on average, twice as expensive. Countries projected to rapidly expand their engineering investments while losing natural capital will be most constrained in realizing green-gray water management. The situation is expected to be most restrictive across the developing world, where the economic, technical, and governance capacities to overcome such challenges remain limited. Our results demonstrate that policies that support blended green-gray approaches offer a pathway to future global water security but will require a strategic commitment to preserving natural capital. Absent such stewardship, the costs of water resource infrastructure and services will likely rise substantially and frustrate efforts to attain universal and sustainable water security.